Pediatric eye emergency department activity during the first wave of Covid-19 pandemic - Elia Franzolin; Rosa Longo; Elena Gusson; Benjamim Ficial; Giorgio Marchini (BMC, 2021)
Abstract Background We investigated the volume and the characteristics of pediatric eye emergency department (PEED) consultations performed at our tertiary eye center during the early months of the COVID-19 pandemic and we compared them to those carried out in the same time interval of the previous three years. Methods Ophthalmic emergency examinations of patients aged ≤18 years old and done during the national COVID-19 lockdown (March 9th, 2020 - May 3rd, 2020) and in the corresponding date range of the previous three years (2017, 2018, and 2019) have been considered and reviewed. The following features were retrieved and analyzed: age, gender, duration and type of accused symptoms, traumatic etiology, and the discharge diagnosis. Results 136, 133, and 154 PEED visits have been performed respectively in 2017, 2018, and 2019, while 29 patients presented in 2020. Therefore, the volume of PEED activity decreased by 79.4% (p < 0.0001). Demographical and clinical characteristics were comparable to those of the pre-COVID period. Despite the absolute reduction in the number of traumas, urgent conditions increased significantly from 30.7 to 50.7% (p = 0.024). Conclusions PEED activity decreased consistently after the onset of the pandemic and it was mainly attended by those children whose conditions required prompt assistance, reducing the number of patients diagnosed with milder pathologies. At the end of the emergency, better use of PEED could avoid overcrowding and minimize waste, allowing resource optimization for the management of urgent cases.